Bipartite Graphs Related to Mutually Disjoint S-Permutation Matrices. (9th December 2012) - Yordzhev, Krasimir
Abstract : Some numerical characteristics of bipartite graphs in relation to the problem of finding all disjoint pairs of S-permutation matrices in the general n 2 × n 2 case are discussed in this paper. All bipartite graphs of the type g = 〈 R g ∪ C g, E g 〉, where | R g | = | C g | = 2 or | R g | = | C g | = 3, are provided. The cardinality of the sets of mutually disjoint S-permutation matrices in both the 4 × 4 and 9 × 9 cases is calculated.